A Systematic Review of Resilience and Personality Traits among College Students: Evidence from Global Studies - Verma, Shikha; Singh, Nikita (Revista Review Index Journal of Multidisciplinary, 2025)
The relationship between resilience and personality traits among college students has been a significant area of psychological research over the past decade. This review synthesizes findings from 28 studies conducted between 2010 and 2025 across various countries, exploring correlations between resilience and the Big Five personality factors. Resilience is consistently found to be positively associated with extraversion, conscientiousness, agreeableness, and openness while negatively associated with neuroticism. The studies also highlight gender-specific predictors, such as assertiveness and forgiveness, and emphasize the role of sociability and self-acceptance in shaping resilience. Methodologies include quantitative, correlational, cross-sectional, and longitudinal designs with diverse sample characteristics, ranging from undergraduate and medical students to high school students. The findings provide robust evidence of the interplay between personality traits and resilience, offering practical implications for developing resilience-based interventions in educational settings. However, variations in cultural contexts and measurement tools underline the need for further longitudinal and cross-cultural research to generalize the findings.